A Framework for Prioritizing the TESS Planetary Candidates Most Amenable to Atmospheric Characterization. (27th September 2018) - Kempton, Eliza M.-R.; Bean, Jacob L.; Louie, Dana R.; Deming, Drake; Koll, Daniel D. B.; Mansfield, Megan; Christiansen, Jessie L.; López-Morales, Mercedes; Swain, Mark R.; Zellem, Robert T.; Ballard, Sarah; Barclay, Thomas; et al.
Abstract: A key legacy of the recently launched the Transiting Exoplanet Survey Satellite ( TESS ) mission will be to provide the astronomical community with many of the best transiting exoplanet targets for atmospheric characterization. However, time is of the essence to take full advantage of this opportunity. The James Webb Space Telescope ( JWST ), although delayed, will still complete its nominal five year mission on a timeline that motivates rapid identification, confirmation, and mass measurement of the top atmospheric characterization targets from TESS . Beyond JWST, future dedicated missions for atmospheric studies such as the Atmospheric Remote-sensing Infrared Exoplanet Large-survey ( ARIEL ) require the discovery and confirmation of several hundred additional sub-Jovian size planets ( R p < 10 R ⊕ ) orbiting bright stars, beyond those known today, to ensure a successful statistical census of exoplanet atmospheres. Ground-based extremely large telescopes (ELTs) will also contribute to surveying the atmospheres of the transiting planets discovered by TESS . Here we present a set of two straightforward analytic metrics, quantifying the expected signal-to-noise in transmission and thermal emission spectroscopy for a given planet, that will allow the top atmospheric characterization targets to be readily identified among the TESS planet candidates. Targets that meet our proposed threshold values for these metrics would be encouraged for rapid follow-up and confirmation via radial velocity mass measurements. Based on the catalog of simulated TESS detections by Sullivan et al., we determine appropriate cutoff values of the metrics, such that the TESS mission will ultimately yield a sample of ∼300 high-quality atmospheric characterization targets across a range of planet size bins, extending down to Earth-size, potentially habitable worlds.